2004
DOI: 10.1143/ptps.153.301
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogap of Color Superconductivity

Abstract: We show that the pseudogap of the quark density of states is formed in hot quark matter as a precursory phenomenon of the color superconductivity on the basis of a low-energy effective theory. We clarify that the soft mode of the di-quark pair field gives rise to a peculiar behavior of the quark dispersion relation and a short life-time of the quasiparticles near the Fermi surface, both of which make a depression of the density of states of quarks. Our result suggests that the appearance of the pseudogap is a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
281
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(317 citation statements)
references
References 4 publications
35
281
1
Order By: Relevance
“…On the other hand, various models predict that there exists a discontinuous first order phase transition at nonzero µ B . The existence of the endpoint of the first order transition, the QCD critical point [3], and possibly multiple critical points [4], are anticipated in the phase diagram of QCD on T -µ B plane [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, various models predict that there exists a discontinuous first order phase transition at nonzero µ B . The existence of the endpoint of the first order transition, the QCD critical point [3], and possibly multiple critical points [4], are anticipated in the phase diagram of QCD on T -µ B plane [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In QCD, however, the strong attraction exists in the scaler quark-antiquark channel which leads to a non-perturbative phenomenon called the dynamical chiral condensation in the low density regime. It is interesting to investigate how the incorporation of the dynamical formation of the chiral condensates affects color superconducting phases [27,28]. The competition between the chiral and diquark condensations under the charge neutrality constraints was first investigated in a four-Fermion model [24]; it was shown that the second densest phase next to the CFL strongly depends on the quark-quark (diquark) coupling strength, and in particular, the gapless CFL phase may be washed out from the phase diagram except for an extremely weak coupling case.…”
Section: Introductionmentioning
confidence: 99%
“…Also, at finite density, a renormalization of the chemical potential by the vectorvector interaction is expected, as considered already in the earliest work [15]. The effect of the vector interaction has been discussed in the context of the QCD phase diagram [14,34,17,35,36]. A vector-vector coupling constant as small as only 10 ∼ 20% of the four-fermion coupling constant in the scalar channel is enough to make the critical point disappear from the phase diagram.…”
Section: Phase Diagrammentioning
confidence: 97%